2011
DOI: 10.1021/jp111820b
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Fluorescent Metal (Au, Ag) Nanoclusters Capped in Bovine Serum Albumin Followed by Fluorescence and Spectroscopy

Abstract: Fluorescent noble metal (Au, Ag) nanoclusters have been biolabeled to bovine serum albumin (BSA) by wet chemistry. Spectroscopic and fluorescence investigations relate the role of the pH and the nature of the reducing agent to the size and the oxidation state of metal clusters. Blue-emitting (λ = 450 nm) small gold nanoclusters (eight atoms) prepared at pH 8 weakly bonded to BSA grow at higher pH to form red-emitting (λ = 690 nm) bigger clusters (25 atoms) covalently bonded to BSA via the sulfur group. X-ray p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
232
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 369 publications
(262 citation statements)
references
References 41 publications
25
232
1
Order By: Relevance
“…The short nanosecond range lifetime is usually associated with singlet excited states originating from metal-metal interactions. On the other hand, the long microsecond range lifetime component is typical of triplet excited states 43,57 . This extended high energy state is of interest for analytical applications due to its high sensitivity to the local environment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The short nanosecond range lifetime is usually associated with singlet excited states originating from metal-metal interactions. On the other hand, the long microsecond range lifetime component is typical of triplet excited states 43,57 . This extended high energy state is of interest for analytical applications due to its high sensitivity to the local environment.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the Mattoussi lab reported the preparation of red-emitting Au NCs with a quantum yield of up to 14% when stabilised with bidentate thiolated ligands containing a zwitterionic group 40 . NC features such as tunable photoluminescence [41][42] , multiexponential fluorescence lifetime [43][44] , or aggregation induced enhancement 45 have been extensively studied with potential applications in the fields of sensing 46 , bioimaging 47 and optics 48 . Other interesting properties of NCs relevant for therapeutic applications rely on their ultra-small size, low toxicity and stability in physiological media.…”
Section: Introductionmentioning
confidence: 99%
“…Formation of such nanoparticle in a protein template or attached to protein should not cause increase in the BSA size by 2.5 nm. This indicates that the size increase after synthesis could be due to the transformation of the secondary structure of BSA induced by formation of a gold nanocluster inside the protein [30].…”
Section: Discussionmentioning
confidence: 98%
“…In literature it was reported that BSA-Au NCs fluoresce in the red spectral region [4, 14-16, 30, 37] and the PL band at 640-700 nm corresponds to the PL of Au NCs that are formed inside BSA. Some papers reported that during synthesis two types of photoluminescent BSA-Au NCs are formed: blue photoluminescent NCs (PL λ max ~ 470 nm) and red photoluminescent NCs (PL λ max ~ 660 nm) [4,30,38]. However, it should be noted that these authors used ascorbic acid as a reducing agent.…”
Section: Discussionmentioning
confidence: 99%
“…As depicted in Fig. 6, the XPS spectrum in the absence of H 2 O 2 shows an Au 4f band at binding energies of 83.9 and 87.6 eV assigned to 4f 5/2 and 4f 7/2 , which could be attributed to Au(0)state [39]. When reacted with H 2 O 2 , the peak gradually shifts to a higher binding energy level, which can be ascribed to higher oxidation states of Au [33].…”
Section: Resultsmentioning
confidence: 92%